2021
DOI: 10.11591/ijeecs.v22.i1.pp129-136
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of a stability control system for TCP/AQM network

Abstract: <p><span>In this work, we used a new approach as active queue management (AQM) to avoid data congestion in TCP/IP networks. The new approach is PSO-PI controller which use the proportional-integral controller as a control unit and particle swarm optimization (PSO) algorithm as an optimization technique to improve the performance of the PI controller and therefore improving the performance of TCP/IP networks as a required goal. The optimization control (PSO-PI) is characterized by access to design a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…The internet contains routers, and one of its tasks is to store data or packets, i.e., put an active queue management (AQM) queue before conducting [16]. The routing process after the required path is available, which includes through an algorithm that fits its work [17].…”
Section: Introductionmentioning
confidence: 99%
“…The internet contains routers, and one of its tasks is to store data or packets, i.e., put an active queue management (AQM) queue before conducting [16]. The routing process after the required path is available, which includes through an algorithm that fits its work [17].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is the large number of data as a result of the large number of users, which causes congestion resulting from the waiting list [7]- [9]. Multiple transmitting sources make the network congested, in addition to multiple receiving sources, speed and time are among the factors involved in evaluating the size or smallness of the problem [10]- [12]. Various methodologies have been developed to deal with all the problems and to control congestion caused by overload on the network [13]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that GAC and FLC were more accurate and efficient than PIDC. The work depended on FSMC and GAs to control an AQM network to improve computer network performance by providing effective queue management [27]. Some studies have been conducted that simulated the adoption of non-linear systems, which is important in order to improve work performance by using traditional and expert control methods, which enables the researchers to control system behavior and obtain a balance with the changes in the operation of the system [24].…”
Section: Introductionmentioning
confidence: 99%